Eliminating intercrystalline side effects for stable lithium metal batteries - Xingwei Sun; Yang Feng; Jiangtao Yu; Yong Lu; Shuo Xu; Ying Jiang; Haixia Li; Zhenhua Yan; Kai Zhang; Jun Chen (Proceedings of the National Academy of Sciences, 2025)
Lithium metal is widely recognized as the ultimate anode material for next-generation lithium batteries due to its superior specific capacity. However, microscopic crystallographic heterogeneity caused by crystal faces and grain boundaries leads to nonuniform lithium deposition, thereby undermining the stability of lithium metal anode. This study systematically investigates the intricate impact of grain boundaries on the structural characteristics, deposition behavior, and electrochemical properties of lithium metal. We demonstrate that grain boundaries serve as preferential nucleation sites, exacerbating morphological heterogeneity. Although eliminating preexisting grain boundaries from substrate facilitates homogeneous lithium nucleation and enhances electrochemical performance, this approach does not address the deposition issues originating from the intercrystalline regions of newly deposited grains. Furthermore, the continuous expansion of the intercrystalline network disrupts single-crystal structure and accelerates anode degradation, imposing a critical constraint on performance enhancement. This work unveils a previously overlooked intercrystalline-driven failure mechanism and provides insights for realizing dendrite-free lithium batteries.